2023
DOI: 10.1037/dev0001590
|View full text |Cite
|
Sign up to set email alerts
|

Children’s implicit gender–toy association development varies across cultures.

Miao Qian,
Wang Ivy Wong,
A. Natisha Nabbijohn
et al.

Abstract: Gender-stereotyped beliefs develop early in childhood and are thought to increase with age based on prior research that was primarily carried out in Western cultures. Little research, however, has examined cross-cultural (in)consistencies in the developmental trajectory of gender-stereotyped beliefs. The present study examined implicit gender–toy stereotypes among 4- to 9-year-olds (N = 1,013; 49.70% girls) in Canada, China, and Thailand. Children from all three cultures evidenced implicit gender–toy stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have shown the consistency of gender stereotypes across Chinese and Western cultures in general (Wong & VanderLaan, 2020; Yu et al, 2010), such as the concepts of masculinity and femininity (Cheung, 1996), toy play (Qian et al, 2023; Todd et al, 2018), and color preferences (Yeung & Wong, 2018). Despite the evidence supporting the similarity in gender socialization in Chinese and Western cultures, we acknowledge that there are limitations in making cross-cultural comparisons between Hong Kong and Canadian children in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown the consistency of gender stereotypes across Chinese and Western cultures in general (Wong & VanderLaan, 2020; Yu et al, 2010), such as the concepts of masculinity and femininity (Cheung, 1996), toy play (Qian et al, 2023; Todd et al, 2018), and color preferences (Yeung & Wong, 2018). Despite the evidence supporting the similarity in gender socialization in Chinese and Western cultures, we acknowledge that there are limitations in making cross-cultural comparisons between Hong Kong and Canadian children in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing the authors’ White, cisgender, European background, we agree that the cultural and social/societal setting needs to be addressed when sex and gender are being discussed. For example, the emergence of gender stereotypes during childhood varies markedly depending on cultural background ( 9 ), and across different cultures, sex and gender may be expected to play differently accentuated or even diverging roles in mental well-being and disorders ( 10 ). The inclusion of individuals from diverse cultural contexts and invested in different gender cultures and policies is therefore of great relevance for our research, whereas a purely Western perspective will significantly limit what we can achieve.…”
mentioning
confidence: 99%